The Other Against the World: On the Fiction of Ariana Harwicz - Crespi, Maximiliano (2021)
This paper presents a critical analysis of the narrative of the writer Ariana Harwicz from a theoretical perspective based on Fredric Jameson´s studies on the political unconscious and literary ideology. The analysis is developed for the five novels produced by the author in the last ten years.